THE EFFECTS OF ACUTE PHYSICAL EXERCISE TRAINING ON MATHEMATICAL COMPUTATION IN CHILDREN - Gustav Bala (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2014)
The aim of this study was to determine whether acute physical exercise may increase the ability of young children to quickly solve basic mathematical problems. The participants who took the basic mathematics test before and after physical exercise included 288 preschool children, 128 children from school institutions, and 13 from a special needs school (mildly mentally disabled children, ages 13-14). The participants who took the basic mathematics test without employing physical exercise included 18 children from pre-school and 67 from school institutions. The results showed that the children's computation performance was enhanced significantly in the groups with 30, or 45, or 60 min of physical exercise, but not in the groups without physical exercise. This means that even acute intensive physical training can yield positive effects on children's mathematical abilities.